A bibliometric retrospection of cash waqf from the lens of Scopus database (1979-2023) - Ahmad, Nor Halawah; Mokhlas, Hasmi; Yahya, Ros Anita; Ali, Siti Mariam; Ahmad, Siti Nurul Akma (2023)
The present study undertakes to develop a meaningful single-source reference for management and organization scholars interested in using bibliometric methods for mapping research specialties. This study employs a bibliometrics approach to explore the evolution and trend in cash waqf by considering the first year it was published until today. There were 82 articles retrieved from the Scopus database between 1979 to 2023. Economics and finance were the most studied area followed by social sciences which both contributed 38 numbers of publications each. The findings also revealed a clear interest among Asian countries in studying cash waqf which was pioneered by Muslim-majority countries, particularly Malaysia and Indonesia. Undoubtedly, both countries have always been referred to by neighboring countries and other Islamic continents for their practices and implications. This study has limitations. The study includes a range of data retrieved from the Scopus database only and lacks representation from other sources of databases such as Web of Science, Google Scholar, and others. The result of this study might contribute to the body of knowledge on delivering comprehensive trend analysis of the studies related to cash waqf.